Reviews of Physiology, Biochemistry and Pharmacology 166 - Nilius, Bernd; Gudermann, Thomas; Jahn, Reinhard; Lill, Roland; Offermanns, Stefan; Petersen, Ole H. (Reviews of Physiology, Biochemistry and Pharmacology, 2014)
Contents A. Verkhratsky, R. C. Reyes, and V. Parpura TRP Channels Coordinate Ion Signalling in Astroglia. A. Nürnberg, A. Kollmannsperger, and R. Grosse Pharmacological Inhibition of Actin Assembly to Target Tumor Cell Motility.   C. A. Goodman The Role of mTORC1 in Regulating Protein Synthesis and Skeletal Muscle Mass in Response to Various Mechanical Stimuli.